Survey of the Use of Qawaid Fiqhiyah in Current Cases in the Fields of Worship, Mu'amalah and Siyasah - Putra Eka Zakran (ISNU Nine-Star Multidisciplinary Journal, 2024)
Qawaid fiqhiyah are the principles of Islamic law which are used as guidelines in resolving various problems that arise in life, especially in the areas of worship, mu'amalah, and siyasah. As time goes by, the application of qawaid fiqhiyah in actual cases is increasingly relevant to study in order to understand how these principles are applied in the context of contemporary Islamic law. This research aims to analyze the use of qawaid fiqhiyah in various actual cases in three main areas: worship, mu'amalah, and siyasah, as well as assessing the extent to which these rules are able to provide legal solutions that are in accordance with the principles of Islamic justice. This research uses normative legal methods with a conceptual and statutory approach. Data was obtained through literature studies from classical and contemporary fiqh books, as well as analysis of actual cases that occurred in society. The research results show that qawaid fiqhiyah has a significant role in providing a legal basis that is flexible and adaptive to changing times. In the field of worship, principles such as al-masyaqqah tajlibu at-taysir are applied to facilitate the implementation of worship in difficult conditions. In mu'amalah, the principle of al-'adah muhakkamah is the basis for modern economic transactions. While in siyasah, the principle of tasharruf al-imam 'ala ar-ra'iyyah manuthun bil maslahah is used in Islamic government policies. The conclusion of this study is that qawaid fiqhiyah remains relevant in facing the challenges of modern Islamic law. Its application in various fields shows that these principles are able to answer actual problems while maintaining the values ​​of Islamic law that are fair and beneficial.